1992
DOI: 10.1093/genetics/132.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between pairing initiation sites, recombination nodules and meiotic recombination in Sordaria macrospora.

Abstract: The decrease of meiotic exchanges (crossing over and conversion) in two mutants of Sordaria macrospora correlated strongly with a reduction of chiasmata and of both types of "recombination nodules." Serial section reconstruction electron microscopy was used to compare the synapsis pattern of meiotic prophase I in wild type and mutants. First, synapsis occurred but the number of synaptonemal complex initiation sites was reduced in both mutants. Second, this reduction was accompanied by, or resulted in, modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(18 citation statements)
references
References 55 publications
1
14
0
3
Order By: Relevance
“…Since SICs assemble prior to SC formation and are still present in a zip1 mutant where SC is absent, Fung et al (2004) concluded that interference in budding yeast can act independently of synapsis. This independence has also been shown in Sordaria (Zickler et al, 1992). A 2006 study showed substantial interference between MSH4 foci in mice with defective SCs, although the data did not allow determination of whether MLH1 foci interfere in the absence of the SC (de Boer et al, 2006).…”
Section: Synaptonemal Complexmentioning
confidence: 77%
“…Since SICs assemble prior to SC formation and are still present in a zip1 mutant where SC is absent, Fung et al (2004) concluded that interference in budding yeast can act independently of synapsis. This independence has also been shown in Sordaria (Zickler et al, 1992). A 2006 study showed substantial interference between MSH4 foci in mice with defective SCs, although the data did not allow determination of whether MLH1 foci interfere in the absence of the SC (de Boer et al, 2006).…”
Section: Synaptonemal Complexmentioning
confidence: 77%
“…It must be emphasized that, unlike noteworthy cases in yeast (ENGEBRECHT et al 1990) and Sordaria (ZICKLER et al 1992) which have been studied, the close rela-tionship of homologous synapsis here to the occurrence of crossing over is strictly a relationship to reciprocal recombination, not conversion, although many of the crossovers may also be associated with conversion. However, strong relationship of existence of overall homologous synapsis to conversion only events has been found in the mer1 mutant of yeast in cases where some of the usual defects are corrected by presence of the MER2 gene in high copy number.…”
Section: Discussionmentioning
confidence: 78%
“…At zygotene in material with large chromosomes, initiation of meiotic pairing and synapsis are accompanied by the appearance of SC-associated nodules which are generally smaller and much more numerous but otherwise appear similar to pachytene RNs (ALBINI andJoms 1987; . Some studies have suggested correlation between pairing initiation sites and positions of RNs, chiasmata and recombination (ZICKLER et al 1992;STACK et al 1993). ZICKLER et al (1992) found correlations between frequency and location of reciprocal exchanges and frequency and location of late RNs in wild-type Sordaria but disparity between location of nodules and exchanges in those mutants which cause reduction in recombination but do not cause SC arrest or major abnormalities.…”
mentioning
confidence: 99%
“…These models are compatible with the nonequivalence observed for the translocation chromosomes in C. elegans, if one postulates that the HRR pairs homologs from a distance, followed by DNA homology searches to promote synapsis and synaptonemal complex formation based on DNA sequence. Alternatively, the HRR could be required following a DNA homology search, perhaps as the region where synapsis initiates (e.g., ZICKLER et al 1992). If the HRR were a loading site for synaptonemal complex or recombination proteins, translocations and insertions might be expected to suppress recombination by blocking the progression of the complex.…”
Section: Discussionmentioning
confidence: 99%